Penelusuran Minat dan Bakat Olahraga pada Siswa Sekolah Menengah Pertama di Kabupaten Pekalongan (Universitas Negeri Semarang, 2021)
The background of this research is the unknown sporting talents of students, the suitability of student interests and talents, the lack of physical education teacher knowledge about scouting for sports search talent methods, and coaching that is not optimal. The purpose of this study: to determine talent and compatibility with the interests of junior high school sports in Pekalongan Regency in the academic year 2019/2020. This research approach uses quantitative descriptive methods. Data collection techniques use: (1) Sport search talent tests are used to find out the talents students have, (2) Interviews are used to confirm the results of the sport search talent tests. The population in this study were junior high school students in Pekalongan Regency. The sampling technique uses purposive sampling. Analysis of the data in this study used descriptive percentages. Data processing using the sport search software application. From the results of the analysis of the data obtained a number of 19 students or 15.3% of test takers have an interest in accordance with their talents and 105 students or 84.7% of test takers have an interest that is not in accordance with their talents. The conclusion is that junior high school students in Pekalongan Regency have various sports talents, but some of these potentials are not in accordance with the interests of students. With this research, it is hoped that it will become a reference or alternative for the guiding process and the development of sports talent in Pekalongan Regency.